2011
DOI: 10.3813/aaa.918450
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Assessment of Upright Piano Key Vibrations

Abstract: Acceleration measurements of ag roup of pianos have shown significant differences in keyv ibration levels between upright and grand pianos. These differences suggest the possibility of improving the upright piano by reducing keyvibrations. This wasachievedbyreplacing an upright keybed with one made of amaterial giving higher mechanical impedance. Agroup of experienced pianists evaluated apair of pianos, one of which wasfitted with the replacement keybed. The participants consistently preferred the modified pia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
(7 reference statements)
1
15
0
Order By: Relevance
“…Similar tonal components were observed across the two piano types, but upright pianos showed a stronger broadband component, which could explain the generally lower perceived quality of upright versus grand pianos. In fact, a later study showed that pianists preferred the tone quality and loudness profile of an upright piano with attenuated broadband vibrations [39].…”
Section: Vibrations In the Acoustic Pianomentioning
confidence: 99%
“…Similar tonal components were observed across the two piano types, but upright pianos showed a stronger broadband component, which could explain the generally lower perceived quality of upright versus grand pianos. In fact, a later study showed that pianists preferred the tone quality and loudness profile of an upright piano with attenuated broadband vibrations [39].…”
Section: Vibrations In the Acoustic Pianomentioning
confidence: 99%
“…In traditional musical instruments, the tactile and kinaesthetic feedback coming from the resonating parts of the instrument give the performer important information about their interaction [1,20,28,43] (see Chap. 2).…”
Section: Haptic Feedback In Music Technologymentioning
confidence: 99%
“…In a subsequent experiment [5], a modified upright piano was built using materials with higher mechanical impedance, reducing the broadband component of the key vibrations. Results showed that pianist rated the modified piano better than an original one, but their remarks focused on improvements in the loudness and tone of the sound (which were measured to be equal in both pianos), while no comments were made about the vibration sensation.…”
Section: Motivationsmentioning
confidence: 99%
“…Notch filter at 492Hz 2 Notch filter at 197Hz and 738Hz 3 Notch filter at 492Hz and 738Hz 4 Notch filter at 197Hz, 492Hz and 738Hz String 5 1 Notch filter at 109Hz 2 Notch filter at 109Hz applied three times 3 Notch filter at 548Hz 4 Notch filter at 109Hz, 548Hz and 659Hz Using the accelerometer and a National Instruments USB-4431 acquisition card 5 we recorded the vibration produced by the plucking of a string using a pick. Two strings were selected, the second (tuned at B 3 , 246.94Hz) and the fifth (tuned at A 2 , 110Hz) and four takes of each were recorded at 48000Hz sampling rate.…”
Section: String 2mentioning
confidence: 99%
See 1 more Smart Citation